ALK-Positive Renal Cell Carcinoma in a Large Series of Consecutively Resected Korean Renal Cell Carcinoma Patients - Lee, Cheol (The Korean Society of Pathologists and The Korean Society for Cytopathology, 2013)
BACKGROUND: Recently, there have been a few reports of renal cell carcinoma (RCC) cases with anaplastic lymphoma kinase (ALK) gene fusion. In this study, we screened consecutively resected RCCs from a single institution for ALK protein expression by immunohistochemistry, and then we performed fluorescence in situ hybridization to confirm the ALK gene alteration in ALK immunohistochemistry-positive cases. METHODS: We screened 829 RCCs by ALK immunohistochemistry, and performed fluorescence in situ hybridization analysis using ALK dual-color break-apart rearrangement probe. Histological review and additional immunohistochemistry analyses were done in positive cases. RESULTS: One ALK-positive case was found. Initial diagnosis of this case was papillary RCC type 2. This comprises 0.12% of all RCCs (1/829) and 1.9% of papillary RCCs (1/53). This patient was a 44-year-old male with RCC found during routine health check-up. He was alive without evidence of disease 12 years after surgery. The tumor showed a papillary and tubular pattern, and showed positivity for CD10 (focal), epithelial membrane antigen, cytokeratin 7, pan-cytokeratin, PAX-2, and vimentin. CONCLUSIONS: We found the first RCC case with ALK gene rearrangement in Korean patients by ALK immunohistochemistry among 829 RCCs. This case showed similar histological and immunohistochemical features to those of previous adult cases with ALK rearrangement, and showed relatively good prognosis.